2005
DOI: 10.1111/j.1464-410x.2005.05851.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of symptomatic simple renal cysts by percutaneous aspiration and ethanol sclerotherapy

Abstract: 6 months by clinical assessment, US and intravenous urography. Success was defined as complete when there was total ablation of the cyst and partial when there was a recurrence of less than half the original cyst volume with the resolution of symptoms. Failure was defined as the recurrence of more than half of cyst volume and/or persistent symptoms. RESULTSAfter aspiration and ethanol sclerotherapy, there was microscopic haematuria in two patients and low-grade fever ( < 38.3 ° C) in two, but no major complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 24 publications
3
59
0
5
Order By: Relevance
“…Sample size calculations were made by using the results from previous ethanol lavage of hepatic and renal cysts, [9][10][11][12] published pilot data of ethanol lavage of pancreatic cysts, 24 and expected clinical response to 1 ethanol (80%) lavage compared with 1 saline solution lavage. We estimated that 1 saline solution and 1 ethanol lavage would lead to a 20% and 80% decrease in cyst surface area (calculated for a sphere by using the formula 4pr 2 , where r is the cyst radius), respectively, as measured by EUS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample size calculations were made by using the results from previous ethanol lavage of hepatic and renal cysts, [9][10][11][12] published pilot data of ethanol lavage of pancreatic cysts, 24 and expected clinical response to 1 ethanol (80%) lavage compared with 1 saline solution lavage. We estimated that 1 saline solution and 1 ethanol lavage would lead to a 20% and 80% decrease in cyst surface area (calculated for a sphere by using the formula 4pr 2 , where r is the cyst radius), respectively, as measured by EUS.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is a common phenomenon after ethanol injection of hepatic, renal, and thyroid cysts. [9][10][11][12][13] Acute pancreatitis after ethanol lavage of a pancreatic cyst probably resulted from extravasation of the ethanol out of the cyst and into either the parenchyma or pancreatic duct. In both patients in our study with acute pancreatitis, hospitalization and uneventful discharge occurred after 2 days and 10 days, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 In 2005, Gan et al 21 showed that ethanol lavage of pancreatic cystic lesions was safe and effective. Since this study, there have been few experimental studies looking at injection of ethanol 18 or ethanol plus paclitaxel in attempts to ablate pancreatic cysts.…”
mentioning
confidence: 98%
“…Single or multiple sessions have been used, with better results but with higher complications for multiple sessions [363, 366, 373 -377]. The time of exposure (in-dwell time) to ethanol varies from 3 minutes to 4 hours, most often around 20 minutes [352,363,373,375,377,378]. The volume of ethanol injected following aspiration varies from 20 -50 % of the cyst volume and the maximum dose from 75 -200 mL.…”
Section: Ethanol Sclerotherapymentioning
confidence: 99%